2012
DOI: 10.1145/2378956.2378960
|View full text |Cite
|
Sign up to set email alerts
|

Enabling content-aware traffic engineering

Abstract: Today, a large fraction of Internet traffic is originated by Content Delivery Networks (CDNs). To cope with increasing demand for content, CDNs have deployed massively distributed infrastructures. These deployments pose challenges for CDNs as they have to dynamically map end-users to appropriate servers without being fully aware of the network conditions within an Internet Service Provider (ISP) or the end-user location. On the other hand, ISPs struggle to cope with rapid traffic shifts caused by the dynamic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 24 publications
(18 reference statements)
1
43
0
Order By: Relevance
“…Furthermore, Refs. [7], [47] show that the ISPs should perform adequate routing and enduser redirection in small time scales, and the traffic matrix should be considered as a parameter for the network path selection [51]. Subsequently, the obtained results showed that, by placing SoRs at the edges of ISP networks, the SoRs could be used to leverage DNS-based CDN redirection to achieve end-user redirection in small time scales.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, Refs. [7], [47] show that the ISPs should perform adequate routing and enduser redirection in small time scales, and the traffic matrix should be considered as a parameter for the network path selection [51]. Subsequently, the obtained results showed that, by placing SoRs at the edges of ISP networks, the SoRs could be used to leverage DNS-based CDN redirection to achieve end-user redirection in small time scales.…”
Section: Discussionmentioning
confidence: 99%
“…As previously stated, various studies such as Refs. [7], [8], [9], [11] pointed out the necessity of ISP-CDN collaboration to achieve this objective. ISP-CDN collaboration can be explained as the process that ensures the end-users are redirected to the best server via the best path.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations